2008
DOI: 10.1002/pros.20859
|View full text |Cite
|
Sign up to set email alerts
|

Transition zone and anterior stromal prostate cancers: Zone of origin and intraprostatic patterns of spread at histopathology

Abstract: BACKGROUND.To describe the precise location of transition zone (TZ) and anterior fibromuscular stroma (AFMS) prostate cancers (TZ/AFMS) within histological zones at various stages of development and to demonstrate their pattern of intraprostatic spread from their site of origin. METHODS. Anterior TZ/AFMS cancers excluding the anterolateral part of peripheral zone, were identified from radical prostatectomy specimens. Morphometric histopathological study included largest surface area, volume and spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 18 publications
4
55
0
2
Order By: Relevance
“…In this study, an additional 123 patients, corresponding to 12% of the initial cohort, were diagnosed with prostate cancer after undergoing a second, third, or fourth repeat biopsy (4). The TRUS-guided biopsy technique is known to frequently overlook cancers in the anterior region of the prostate, where approximately 30% of cancers reside (5). Therefore, the false negative rate of TRUS-guided biopsies is a major concern.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an additional 123 patients, corresponding to 12% of the initial cohort, were diagnosed with prostate cancer after undergoing a second, third, or fourth repeat biopsy (4). The TRUS-guided biopsy technique is known to frequently overlook cancers in the anterior region of the prostate, where approximately 30% of cancers reside (5). Therefore, the false negative rate of TRUS-guided biopsies is a major concern.…”
Section: Discussionmentioning
confidence: 99%
“…A cancer was considered as originated from transition zone if 470% of its surface was located in this zone, as previously described. 15,22 A transition zone prostate cancer was identified in 62/397 (16%) patients who constituted our study population. Patients were diagnosed through PSA screening and/or digital rectal examination.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, transition zone tumors and cancers arising in the most anterior horns of the peripheral zone have been further characterized and grouped together under the designation of 'anterior-predominant prostatic tumors,' to be distinguished from those arising in the posterior peripheral zone. 21 Lately, Bouye et al 22 have studied the zone of origin and patterns of spread of anterior prostate cancers, comprising tumors of transition zone and anterior fibromuscular stroma, and concluded that the contours and location of these cancers are predictable and conform to histological zones boundaries. Transition zone tumors are rarely unifocal and are often associated with peripheral zone cancer foci.…”
mentioning
confidence: 99%
“…2 The negative predictive value was 95 %. Mean cancer volume detected at MRI was 2.44 ml (range 0.02-14.5) and mean cancer volume not detected at MRI was 0.16 ml (range 0.01-2.4).…”
Section: Multiparametric Magnetic Resonance Imagingmentioning
confidence: 96%